Association of Physician Densities and Gynecologic Cancer Outcomes in the United States. Issue 5 (5th November 2022) - Smick, Alexandra H.; Holbert, Michael; Neff, Robert
Abstract : Increasing primary care physician density is associated with earlier stage at diagnosis and improved 5-year survival rates for cervical cancer. Abstract : OBJECTIVE: To evaluate whether there is an association between county-level obstetrician–gynecologist (ob-gyn) and primary care physician (PCP) densities and gynecologic cancer outcomes in the United States. METHODS: A retrospective cohort study of gynecologic cancers (uterine, ovarian, and cervical) in the Surveillance, Epidemiology, and End Results (SEER) database was performed from 2005 to 2018. County-level demographics were abstracted from the SEER database, population density from the United States Census Bureau, and physician density (ob-gyns and PCPs/100, 000 females) from the Area Health Resources File. Backward stepwise regression models were used. RESULTS: Final analysis included 113, 938 patients for stage at diagnosis analysis and 98, 573 patients for 5-year survival analysis. Uterine, ovarian, and cervical cancers represented 60.0%, 25.0%, and 15.0% of patients, respectively. Most counties (57%) were nonmetropolitan and had a mean ob-gyn density of 8 per 100, 000 females and a mean PCP density of 89 per 100, 000 females. Multivariate analysis showed that increasing PCP density was associated with earlier stage at diagnosis (95% CI −6.27 to −0.05; P <.05) and increased 5-year survival rates in cervical cancer (95% CI 0.03–0.09; P <.05). Obstetrician–gynecologist density was not found to affect stage or survival outcomes for uterine or ovarian cancer. Analysis of sociodemographic factors for cervical cancer showed that median household income was negatively correlated with stage ( P =.01) and that the percentage of those with bachelor's degrees and metropolitan status were positively correlated with 5-year survival rates ( P <.01). For uterine cancer, the percentage of Black females was positively correlated with stage ( P <.01) and negatively correlated with 5-year survival rates ( P <.01). CONCLUSION: Increasing PCP density, but not ob-gyn density, is associated with earlier stage at diagnosis and improved 5-year survival rates in cervical cancer. County-level sociodemographic factors, including population diversity, metropolitan status, educational attainment, and household income, were also correlated with outcomes across all cancer types. Targeting PCP supply and education in lower density counties may improve population-based care for cervical cancer.